3-[1-(3-Hydroxybenzyl)-1H-benzimidazol-2-yl]phenol - Eltayeb, Naser Eltaher (International Union of Crystallography, 2009)
In the title molecule, C(20)H(16)N(2)O(2), the benzimidazole mean plane forms dihedral angles of 56.55 (3) and 81.65 (4)° with the two benzene rings. In the crystal structure, intermolecular O—H⋯O and O—H⋯N hydrogen bonds link the molecules into layers parallel to the (101) plane. The crystal packing also exhibits weak intermolecular C—H⋯O and C—H⋯π interactions.